Self-selection into teaching: the role of teacher education institutions - Stefan Denzler; Stefan C. Wolter (Institute for the Study of Labor (IZA), 2008)
Good teachers are critical for a high-quality educational system. This in turns leads to the question of who is interested in going into the teaching profession. Although research has been done on the professional careers of teachers, the issue of self-selection into teacher education has been mostly overlooked until now. The analyses contained in our study are based on a representative sampling of over 1500 high-school students in Switzerland shortly before graduation. The findings indicate that there is a self-selection process with regard to courses of study at teaching training institutions, which is reinforced by institutional and structural characteristics of the types of higher education institutions and the courses of study they offer. This can clearly be seen in comparison with high-school students preparing to study at another type of higher educational institution (university). Accordingly, the findings of this paper tend to indicate that the choices made by future teachers depend to a large extent also on where and how teachers are trained.
urn:nbn:de:101:1-20080527256
Keywords: I2; 370; Teacher education; teacher training; teacher education colleges; self-selection; study choice; occupational choice; Studierende; Berufswahl; Lehrkräfte; Berufsausbildung; Bildungseinrichtung; Schweiz